The Effect of Education Level and Accounting Understanding Moderated by Digital Literacy on Interest in Preparing Financial Reports of Micro-Enterprises - Putri, Negina Kencono; V. Salsabila, Lidhya (Proceeding International Conference on Religion, Science and Education, 2025)
Micro, Small and Medium Enterprises (MSMEs) have an important role in the economic growth of countries throughout the world. The existence of MSMEs, has not been free from obstacles. One of the obstacles is related to the preparation of financial reports. Some small businesses consider that financial reports are not important. This research was conducted to determine the factors that influence interest in preparing financial reports, moderated by digital literacy in micro enterprises. The theory used in this research is Theory of Planned Behavior. The research uses primary data through questionnaires distributed directly and online using a 1-5 Likert scale measuring tool, and data processed using Moderated Regression Analysis. Based on the research results, it was found that education level and level of accounting understanding has effect on interest in preparing financial reports. While digital literacy also has effect on interest in preparing financial reports. The level of education which is moderated by digital literacy, and level of accounting understanding which is moderated by digital literacy has effect on interest in preparing financial reports for micro businesses.